Conservative management of an acute spinal epidural hemorrhage in a child with hemophilia a with inhibitor. Issue 8 (December 2016) - Erkutlu, Ibrahim; Bay, Ali; Aktekin, Elif
Abstract : Hemophilia A is an inherited, X-linked, recessive disorder caused by deficiency of clotting factor VIII. Central nervous system hemorrhage is an uncommon complication in patients with hemophilia. We report the case of a 5-year-old child who had intraspinal hematoma with nonsurgical, conservative management. It should be kept in mind that the optimal management is decided according to patient's condition because of high morbidity and mortality.